Assessment of the ecological sustainability of river basins based on the modified the ESHIPPOfish model on the example of the Velika Morava basin (Serbia, Central Balkans) - Simić, Vladica; Bănăduc, Doru; Curtean-Bănăduc, Angela; Petrović, Ana; Veličković, Tijana; Stojković-Piperac, Milica; Simić, Snežana (Frontiers in Environmental Science, 2022)
This study examines the ecological sustainability of the Velika Morava River Basin (Serbia, Central Balkans) under modern conditions of multiple freshwater stressors, including climate change. The impact of stressors on the ecological services of the river basin is considered, including: drinking water, irrigation, recreation, tourism, ecotourism, and fishing. In order to assess the ecological sustainability of the river basin, a modification of the ESHIPPO model was performed. The essence of the modification is a change to the ES component, which, in the basic model, assesses the degree of ecological specialization of a taxon; and in the modified assessment of the ecological stability of the ecosystem (ESE). The structure of ichthyocenosis is used as the basic biological indicator for the assessment of ESE. The assessment of river basin sustainability was obtained as the difference between ESE and the impact of multiple factors, including: habitat change, invasive species, pollution, human population growth (social factors), and the over-exploitation of resources (HIPPO). The statistical analysis (SOM—Self Organizing Map) highlights the most reliable indicators of both biotic (ichthyocenosis structure elements) and the indicators that best detect the influence of HIPPO factors. The structure of the model is based on general and easily measurable indicators, which enables its application in any river basin in the world. The results of the model indicate that 80% of the studied basin is ecologically unsustainable and that its potential environmental services are greatly reduced.